How Ogilvy and Mather is using the ‘First-mover Advantage’ in terms of branding ‘Teletalk 3G’ and creating brand preference among the customers comparing to MTNL 3G’s first mover advantage - Rafiq, Farzana Bint-E (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.